Motivation and emotional praxis: a collaborative autobiographical narrative of TVET college students from lower socio-economic backgrounds - Motai, Collins Dumisani Morgan (University of the Free State, 2020)
In this qualitative study, I focused on understanding the role of emotions in promoting social justice for students from lower socio-economic backgrounds at TVET colleges. The study also looked at the possibility of decolonising TVET colleges by focusing on emotional experiences and enhancing learning motivation for students from lower socio-economic backgrounds. Consistent with Zembylas’s critical emotional praxis theory, the participants collaboratively shared their stories of emotions encountered in their spaces, and created a collective biography based on emotional experiences, decolonisation, social justice and learning motivation. The collective biography revealed that there are certain emotions and practices that should be taken into consideration when lecturers are working with students from lower socio-economic backgrounds at TVET colleges.
Keywords: Dissertation (M.Ed. (Higher Education Studies))--University of the Free State, 2020; Emotional praxis; Emotions; Lower socio-economic backgrounds; Decolonisation; Social justice; Learning motivation; Collaborative autobiography; Collective biography